The oxidative potential of particulate matter (PM) in different regions around the world and its relation to air pollution sources. Issue 5 (8th July 2022) - Farahani, Vahid Jalali; Altuwayjiri, Abdulmalik; Pirhadi, Milad; Verma, Vishal; Ruprecht, Ario Alberto; Diapouli, Evangelia; Eleftheriadis, Konstantinos; Sioutas, Constantinos
Abstract : Biomass burning and secondary organic aerosols formed by photochemical reactions lead to the highest oxidative potential among urban emission sources and therefore are one of the most hazardous sources in terms of ambient PM toxicity. Abstract : In this study, we investigated the impact of urban emission sources on the chemical composition of ambient particulate matter (PM) as well as the associated oxidative potential. We collected six sets of PM samples in five urban location sites around the world over long time periods varying from weeks to months, intentionally selected for their PM to be dominated by unique emission sources: (1) PM2.5 produced mainly by traffic emissions in central Los Angeles, United States (US); (2) PM2.5 dominated by biomass burning in Milan, Italy; (3) PM2.5 formed by secondary photochemical reactions thus dominated by secondary aerosols in Athens, Greece; (4) PM10 emitted by refinery and dust resuspension in Riyadh, Saudi Arabia (SA); (5) PM10 generated by dust storms in Riyadh, SA, and (6) PM2.5 produced mainly by industrial and traffic emissions in Beirut, Lebanon. The PM samples were chemically analyzed and their oxidative potential were quantified by employing the dithiothreitol (DTT) assay. Our results revealed that the Milan samples were rich in water soluble organic carbon (WSOC) and PAHs, even exceeding the levels measured on Los Angeles (LA) freeways. The PM in Athens was characterized by high concentrations of inorganic ions, specifically sulfate which was the highest of all PM samples. The ambient PM in LA was impacted by the traffic-emitted primary organic and elemental carbon. Furthermore, the contribution of metals and elements per mass of PM in Riyadh and Beirut samples were more pronounced relative to other sampling areas. The highest intrinsic PM redox activity was observed for PM with the highest WSOC fraction, including Milan (biomass burning) and Athens (secondary organic aerosols, SOA). PM in areas characterized by high metal emissions including dust events, refinery and industry, such as Riyadh and Beirut, had the lowest oxidative potential as assessed by the DTT assay. The results of this study illustrate the impact of major emission sources in urban areas on the redox activity and oxidative potential of ambient PM, providing useful information for developing efficient air pollution control and mitigation policies in polluted areas around the globe.